2020
DOI: 10.1039/c9cp05301h
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the heme protein hemoglobin by (−)-epigallocatechin gallate and the study of polyphenol–protein association using multi-spectroscopic and computational methods

Abstract: (−)-Epigallocatechin gallate binds to BHb and exhibits anti-glycating as well as antioxidant behaviors towards glycation and photo-oxidation of BHb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 93 publications
1
26
2
Order By: Relevance
“…The trend in the obtained parameters from steady‐state experiments as listed in Table 1 infers an inverse dependence of K values on temperature. This observation is contrary to what we expect to encounter when static quenching is operational [29,30,32] . This result also opposed the observation made from UV‐Vis absorption study, where the increment of absorption (Figure 1a) led us to conclude the ground‐state complex formation between Lyz and BPS indicating the occurrence of static quenching mechanism [28,29,30] .…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…The trend in the obtained parameters from steady‐state experiments as listed in Table 1 infers an inverse dependence of K values on temperature. This observation is contrary to what we expect to encounter when static quenching is operational [29,30,32] . This result also opposed the observation made from UV‐Vis absorption study, where the increment of absorption (Figure 1a) led us to conclude the ground‐state complex formation between Lyz and BPS indicating the occurrence of static quenching mechanism [28,29,30] .…”
Section: Resultscontrasting
confidence: 99%
“…This observation is contrary to what we expect to encounter when static quenching is operational [29,30,32] . This result also opposed the observation made from UV‐Vis absorption study, where the increment of absorption (Figure 1a) led us to conclude the ground‐state complex formation between Lyz and BPS indicating the occurrence of static quenching mechanism [28,29,30] . However, the intriguing values of k q from Table 1 showed that it is higher than the maximum threshold value of k q for a diffusion‐controlled collision in an aqueous medium (∼10 10 M −1 s −1 ) for dynamic quenching process [30–32] .…”
Section: Resultscontrasting
confidence: 85%
See 2 more Smart Citations
“…They investigated the protein folding mechanism of villin with explicit solvation [42]. Apart from proteins, the technique has been extended to study other relevant biomolecules [43,44] and protein-nanoparticle interactions [45][46][47][48][49]. Simulation of any system revolves around lot of factors.…”
Section: Molecular Dynamics: the Computational Microscopementioning
confidence: 99%